Razmerje med pacientom in zdravnikom: (konferenčni zbornik) : 25. posvet Medicina in pravo, (18.-19. marec 2016, Maribor, Slovenija) (Univerzitetna založba Univerze v Mariboru, 2016)
Conference proceedings at hand include contributions from renowned and reputed experts, domestic and foreign, in the field of medicine and law, as well as of other sciences, the contents of which are influencing those two traditional fields of science, and which can through their content significantly affect the quality and safety of human life. This year’s central theme of the conference is "The relationship between a patient and a doctor." The organizers of the conference are thus re-opening some permanently relevant and some new questions brought about by developments in science, new trends, new perspectives, values, and thoughts on the issues arising from the relationship between a patient and a doctor. At the 25th anniversary of the conference Medicine and Law, the variety and diversity of contributions provide insight into the relationship between a patient and a doctor, for example, in terms of trust in the health-care, media, refugee crisis, liability, significance of explanatory duty, as well as other topics that are once again offering high-quality, current and informative contents.